2012
DOI: 10.2147/cia.s29265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of ultrasound guidance for intra-articular knee injections: a review

Abstract: Intra-articular corticosteroid and hyaluronic acid injections provide short-term symptom amelioration for arthritic conditions involving structural damage or degenerative changes in the knee. Conventional palpation-guided anatomical injections frequently result in inaccurate needle placement into extra-articular tissue and adjacent structures. The purpose of this review was to determine the effect of ultrasound guidance on the accuracy of needle placement, clinical outcomes, and cost-effectiveness in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 33 publications
2
65
0
3
Order By: Relevance
“…Ultrasound guidance of knee injections could be a better option to more precisely deliver the cells intra-articularly. Berkoff et al have reported that ultrasound guidance of knee injections resulted in better IA accuracy of needle placement than anatomical guidance (95.8% versus 77.8%; P  < 0.001) [58]. This enhanced injection accuracy achieved with ultrasound needle guidance directly improves patient-related clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound guidance of knee injections could be a better option to more precisely deliver the cells intra-articularly. Berkoff et al have reported that ultrasound guidance of knee injections resulted in better IA accuracy of needle placement than anatomical guidance (95.8% versus 77.8%; P  < 0.001) [58]. This enhanced injection accuracy achieved with ultrasound needle guidance directly improves patient-related clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the current series received five intra-articular knee injections of sodium hyaluronate, with each injection given 1 week apart. Injections were administered under fluoroscopic guidance, which allows for confirmation of tricompartmental HA distribution and improves injection accuracy, resulting in improved patient outcomes vs. anatomical injection guidance 2123. Patients participated in structured physical therapy and education programs provided by physical therapists 2–3 times per week during the 8-week period.…”
Section: Methodsmentioning
confidence: 99%
“…Berkoff и соавт. [7] провели метаанализ исследований, выполненных до декабря 2011 г., с целью сравнения точности и эффективности внутрисуставных инъекций под УЗконтролем и «вслепую». Надо отметить немногочисленность данных литературы по обсуждаемой проблематике: подобный сравнительный анализ был выполнен лишь в 7 исследованиях [8][9][10][11][12][13][14], при этом максимальное количество наблюдений касалось в основном лечения коленных и плечевых суставов.…”
Section: оценка результатов применения внутрисуставных инъекций под кunclassified
“…Результаты анализа показали, что точность размещения иглы при УЗ-контроле варьировала от 63 до 100%, при инъекции «вслепую» -от 39 до 100%. Точность внутрисуставных инъекций в коленный сустав при УЗ-контроле составила 96,7% против 81,0% без применения УЗ-контроля (p < 0,001); для плечевых суставов эти показатели составили соответственно 97,3 и 65,4% (p < 0,001) [7]. J.S.…”
Section: оценка результатов применения внутрисуставных инъекций под кunclassified